2013
DOI: 10.1089/neu.2012.2613
|View full text |Cite
|
Sign up to set email alerts
|

The Ryk Receptor Is Expressed in Glial and Fibronectin-Expressing Cells after Spinal Cord Injury

Abstract: Wnt proteins play a critical role in central nervous system development and have been implicated in several neuropathologies, including spinal cord injury (SCI). Ryk, an unconventional Wnt receptor, regulates axonal regeneration after SCI, although its expression pattern in this neuropathology remains unclear. Therefore, we sought to define the spatiotemporal and cellular pattern of Ryk expression after a contusive SCI in adult rats using quantitative reverse transcription polymerase chain reaction (RT-PCR), W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 74 publications
1
35
0
Order By: Relevance
“…Interestingly, recent studies carried out in animal models have shown that the Wnt family of proteins, a well-known regulator of crucial processes in the developing [16][17][18] and adult [18][19][20] central nervous system (CNS) under physiological conditions, is also clearly involved in many of the cellular and molecular processes that characterize the progression and outcome of different CNS pathologies [21][22][23][24][25][26][27][28]. Notably, recent studies have described a dysregulation in the expression of several members of this family of proteins in the spinal cord of a mouse model of ALS and also in an in vitro model of the disease [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent studies carried out in animal models have shown that the Wnt family of proteins, a well-known regulator of crucial processes in the developing [16][17][18] and adult [18][19][20] central nervous system (CNS) under physiological conditions, is also clearly involved in many of the cellular and molecular processes that characterize the progression and outcome of different CNS pathologies [21][22][23][24][25][26][27][28]. Notably, recent studies have described a dysregulation in the expression of several members of this family of proteins in the spinal cord of a mouse model of ALS and also in an in vitro model of the disease [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently it was shown to have proapoptotic function in ovarian cancer (Nazarenko et al, ). Ryk is a Wnt binding receptor that mediates axon repulsion in development and inhibition of axon plasticity in adulthood after traumatic injury (Liu et al, ; Keeble and Cooper, ; Keeble et al, ; Schmitt et al, ; Liu et al, ; Miyashita et al, ; Fradkin et al, ; Hollis and Zou, ,; Gonzalez et al, ). Therefore, we elected to characterize these two key regulators of axon growth and plasticity in an animal model of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Given that the effects of Wnt5a in axonal growth are largely dictated by the available receptors in the axonal membrane, 53 axonal level, but also in neuronal somas, reactive astrocytes and microglia/macrophages, NG2+ glial precursors and oligodendrocytes. 3,4,7 These observations indicate that these cell types are able to respond to Wnt5a and, thus, that this Wnt ligand might be influencing their critical responses to SCI. For instance, both Fz5 and Ryk are not only expressed in neurons in the healthy spinal cord but also in adjacent areas to the lesion epicentre after SCI, 3,4 which are thought to be affected by the secondary progression of the injury.…”
Section: Discussionmentioning
confidence: 86%
“…In this sense, we have pression of these Wnt5a receptors can be observed in this cell type after SCI, mainly in those NG2+ cells that are located in the lesion epicenter. 4,7 Finally, since the presence of oligodendroglial and astroglial cells was unaltered in the same time post-injury and rostro-caudal levels, it is plausible that the reduction observed in the accumulation of this cell type in the lesion epicentre might be due to a Wnt5a-mediated decrease in its proliferation and/or survival, rather than an increase in their differentiation rate.…”
Section: Discussionmentioning
confidence: 98%